The Effect of Cash Management and Working Capital Management on Business Sustainability: Evidence from Ferli Confectionery Store in Rambai Kaca Village, Suka Merindu District, Lahat Regency - Sindi Fionika; Elvera Elvera; Zulaiha Zulaiha (The Future of Education Journal, 2026)
This study aims to examine and analyze the impact of cash and working capital management on business sustainability at Ferli’s Candy Store in Rambai Kaca Village, Suka Merindu Subdistrict. Business sustainability is a major challenge for MSMEs amid market fluctuations, making effective financial management a crucial foundation. This study employs a quantitative approach using an associative method and a saturated sample comprising monthly financial data spanning 36 months (2023–2025). Data analysis was conducted using multiple linear regression to test the influence of independent variables on business sustainability. The results indicate that cash management and working capital have a positive and significant effect on business sustainability, both partially and simultaneously. The coefficient of determination (R²) of 0.447 indicates that the variables of cash management and working capital account for 44.7% of the variation in the business sustainability of Toko Manisan Ferli, while the remaining 55.3% is influenced by other factors outside the scope of this study. These findings provide managerial implications for business owners to improve their financial record-keeping systems and strictly separate personal funds from business funds to ensure long-term operational sustainability.